The Use of Sweet Almond Meal as a Protein Source in Japanese Quails Diets - Arjomandi MA; Salarmoini M; Asadikaram G (Poultry Science Journal, 2015)
In the first experiment, the chemical composition, apparent metabolizable energy (AME), AME corrected for nitrogen (AMEn), true metabolizable energy (TME), TME corrected for nitrogen (TMEn) values of the sweet almond meal were determined in adult Leghorn cockerels. The second experiment was performed to evaluate the effects of different levels of sweet almond meal at 0, 100, 200 and 300 g/kg on Japanese quail's growth performance, some blood metabolites, relative weight of different organs, meat quality and egg yolk cholesterol in a completely randomized design with 288 Japanese quails including 4 treatments, 4 replicates and 18 birds per replicate. The metabolizable energy values of sweet almond meal were following: AME = 3734, AMEn = 3648, TME = 3908, TMEn = 3746 kcal/kg as fed basis. Feed intake, feed conversion ratio and live weight gain and relative weight of different organs in the birds fed diets with different levels of the sweet almond meal were not statistically different from control. A sweet almond meal at 300 g/kg level showed the lower serum total cholesterol and low-density lipoprotein (P < 0.05) compared to control and 100 g/kg sweet almond meal. Dietary treatments had no significant effect on the total cholesterol content of quail's eggs. Malondialdehyde concentration in breast meat samples after 40 days freezing decreased, whereas the level of sweet almond meal increased (P < 0.01). In general, a sweet almond meal without any adverse effect on growth performance is a good source of energy and protein and can be used up to 300 g/kg of the Japanese quail diets.